2006
DOI: 10.1007/s00221-006-0705-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of safflor yellow B on brain ischemic injury

Abstract: The present study was conducted to investigate whether safflor yellow B (SYB) had a protective effect on cerebral ischemic injury and to determine the possible mechanisms in vivo and in vitro. In vivo, Male Wistar-Kyoto (WKY) rats were used to make the model of middle cerebral artery occlusion (MCAO). The behavioral test was used to measure neurological deficit scores for evaluation of the ischemic damage of brain. The infarction area of brain was assessed in brain slices stained with 2% solution of 2,3,5-trip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 24 publications
4
34
0
Order By: Relevance
“…About 40% of all AMIs demonstrated S-T segment elevation (Hellermann et al, 2002). A large amount of evidence has demonstrated that C. tinctorius (safflower) or its components possess protective effects against myocardial or cerebral ischemia (Zheng et al, 2003;Wang et al, 2007). In our study, administration of CTI (2.5 and 0.625 g/kg, respectively, for 5 days) could markedly attenuate the increase of ST-segment elevation.…”
Section: Discussionsupporting
confidence: 52%
“…About 40% of all AMIs demonstrated S-T segment elevation (Hellermann et al, 2002). A large amount of evidence has demonstrated that C. tinctorius (safflower) or its components possess protective effects against myocardial or cerebral ischemia (Zheng et al, 2003;Wang et al, 2007). In our study, administration of CTI (2.5 and 0.625 g/kg, respectively, for 5 days) could markedly attenuate the increase of ST-segment elevation.…”
Section: Discussionsupporting
confidence: 52%
“…Our results are consistent with previous work. 21,22 With Leonurine treatment, enhanced activities of SOD and GPx and a decreased level of MDA were observed. A time point study is needed to identify the causality of changes of these biomarkers to identify if it is a direct antioxidant effect of Leonurine.…”
Section: Discussionmentioning
confidence: 97%
“…SY has multiple pharmacological actions such as inhibiting platelet aggregation, anticoagulation, anti-oxidation, and anti-inflammation. [14][15][16][17] It has been reported that HSYA inhibits the phosphorylation of NF-κB and p38 MAPK in BV2 cells in OGD/reoxygeneration (OGD/R) conditions, accompanied by the downregulation of inflammatory IL-1β, IL-6, and TNF-α. 18 Human epithelial cell strain A549 has been stimulated by LPS to activate the TLR4/ Myd88/NF-κB inflammatory pathway, while HYSA also reduces TLR4 expression on mRNA and protein levels.…”
Section: Safflower Yellow Regulates Microglial Polarization and Inhibmentioning
confidence: 99%